Non-canonical Wnt signaling regulates neural stem cell quiescence during homeostasis and after demyelination - Manideep Chavali (Nature Portfolio, 2018)
Following demyelination injury, neural stem cells (NSCs) in the subventricular zone switch to an activated state. Here, the authors show that a transient shift from non-canonical to canonical Wnt signaling is necessary for activation of quiescent NSCs to achieve tissue homeostasis and brain repair.